DETECTION OF QUORUM QUENCHING -PRODUCING BACTERIA FROM RHIZOSPHERE SOIL AS A BIOCONTROL AGENTS - Stella Magdalena; Inez Johanna; Yogiara Yogiara (Teknosains, 2021)
Quorum sensing is known as a communication mechanism among bacteria to control gene expression such as bioluminescence, pigmentation, and pathogenicity. Quorum quenching is known as inhibition of quorum sensing activity. In order to block quorum sensing activity, some bacteria produced enzymes which could degrade AHL, such as AHL-acylase, AHL-lactonase, and AHL-oxidase and reductase. In this study, soil bacteria were isolated and screened for their quorum quenching activity. These isolates were divided into Streptomyces and non-Streptomyces isolates. Detection were done by using Chromobacterium violaceum as an indicator bacteria for pigment inhibition by quorum quenching activity. About 10 out of 695 isolates were shown to possess quorum quenching activity. These isolates were further identified by biochemical tests, Gram staining, and identified by 16S rRNA sequencing. Four positive isolates showed similarity with Streptomyces sp., and 6 positive isolates were non-Streptomyces which showed similarity with Pseudomonas putida, Bacillus pumilus, Bacillus sp., Enterobacter ludwigii, and Enterobacter sp.